LITERASI KEUANGAN DAN PERILAKU KEUANGAN: PERAN VARIABEL MODERASI GRIT - Rohmawati, Lilik; Amaliyah, Erlina Dewi Endah; Prabasari, Bonita (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
The millennial generation connects with massive technological advances and the gigantic use of the internet, this condition requires millennial to make financial decisions quickly and accurately within one click/swab. Without financial literacy, technological advances that bring ease of shopping, ease of using credit cards and pay later will create a consumptive, burdensome debt, unlikely to afford unexpected expense and excessive use of credit cards. This study aims to examine whether financial literacy affects financial behavior of millenial generation with grit as a moderating variable. Using 137 sample of millennials in Semarang, the SPSS 25 analysis was conducted to test hypothesis. Significant relationship not only found between financial literacy and financial behavior of the millennial generation in Semarang. Furthermore, the findings of this study confirms that grit moderates the relationship between financial literacy and financial behavior.